Computing with foresight and industry : 15th Conference on Computability in Europe, CiE 2019, Durham, UK, July 15-19, 2019 : proceedings /: 15th Conference on Computability in Europe, CiE 2019, Durham, UK, July 15-19, 2019 : proceedings. ([2019]) - Unknown
No abstract available